Impact of PVC mixtures of the Electrical Conduit on the Physical Properties - Ismail, AbdelHamid Mohammed Saeed (Journal of natural sciences, life and applied sciences, 2020)
The use of PVC mixtures in the manufacturing of electrical conduit has been employed for a long time along with other materials. In this study, the impact of changing the ratio of the components of the PVC mixtures on the physical properties of the electrical conduit was investigated. The emphasis was placed on three properties: Density, Tensile Strength and Soft Point. The application of the electrical conduit controls the types of materials and their percentages. Physical properties of the PVC products are the most important factors that help to choose compared with other materials. These properties change with the change of the chemical components of the PVC mixture. The study discussed how to enhance and improve these properties by controlling the proportions of some substances in the PVC mixtures. This article aims to demonstrate the strong relationship between PVC polymer, calcium and stabilizers and the physical properties of the electrical conduit. The focus concentrated on three components in the mixture and three physical properties. Random samples were taken to calculate the average percentages of the components in the mixtures. Various tools and several statistical methods were used such as correlation coefficients and scatter charts to prove the relationship between the ratios of the materials and the respective properties. The correlation coefficients between the PVC polymer, stabilizers, calcium, and the density, tensile strength, vicat soft points were (0.92, 0.83, 0.82) respectively. Decreasing the PVC polymer by (17.1%) has caused an increase in the density of the conduit by (2%). Finally, the physical properties of PVC mixtures could be improved by changing component ratios to reach the optimized mixture for the specific application, taking into account other competitive issues such as the final price of the product, environmental impact, and other issues.